ANALISA PERFORMANCE BAN PADA UNIT PRODUKSI OVERBURDEN HD-785 TERHADAP PRODUKTIVITAS TAMBANG BATUBARA - Puspita Sari, Laura (KURVATEK, 2020)
The growing need for coal production led to the greater performance of mechanical tools. In the work of loading and hauling material overburden, the tire's lifetime will be influenced by external and internal conditions. External conditions affecting tire lifetime are road conditions, payload loads that the unit must accept, unit speed and tyre maintenance. While the external condition affecting tire lifetime is the manufacturing tire of the factory that designed it such as Ton Kilometer Per Hour (TKPH) standard used for field operational application. So that the selection of proper tires becomes an important factor for the operation to run smoothly. To minimize the risk of tyre damage, it is necessary to evaluate the performance of tyres by conducting analysis of Key Performance Indicator (KPI) parameters and the ratio of Ton kilometers Per Hour (TKPH) of rating and actual. The results showed that the road condition of the mines that were not well maintenance affected the tire lifetime.